A Single Amino Acid in EBNA-2 Determines Superior B Lymphoblastoid Cell Line Growth Maintenance by Epstein-Barr Virus Type 1 EBNA-2 - Tzellos, Stelios (American Society for Microbiology, 2014)
Sequence differences in the EBNA-2 protein mediate the superior ability of type 1 Epstein-Barr virus (EBV) to transform human B cells into lymphoblastoid cell lines compared to that of type 2 EBV. Here we show that changing a single amino acid (S442D) from serine in type 2 EBNA-2 to the aspartate found in type 1 EBNA-2 confers a type 1 growth phenotype in a lymphoblastoid cell line growth maintenance assay. This amino acid lies in the transactivation domain of EBNA-2, and the S442D change increases activity in a transactivation domain assay. The superior growth properties of type 1 EBNA-2 correlate with the greater induction of EBV LMP-1 and about 10 cell genes, including CXCR7. In chromatin immunoprecipitation assays, type 1 EBNA-2 is shown to associate more strongly with EBNA-2 binding sites near the LMP-1 and CXCR7 genes. Unbiased motif searching of the EBNA-2 binding regions of the differentially regulated cell genes identified an ETS-interferon regulatory factor composite element motif that closely corresponds to the sequences known to mediate EBNA-2 regulation of the LMP-1 promoter. It appears that the superior induction by type 1 EBNA-2 of the cell genes contributing to cell growth is due to their being regulated in a manner different from that for most EBNA-2-responsive genes and in a way similar to that for the LMP-1 gene. IMPORTANCE The EBNA-2 transcription factor plays a key role in B cell transformation by EBV and defines the two EBV types. Here we identify a single amino acid (Ser in type 1 EBV, Asp in type 2 EBV) of EBNA-2 that determines the superior ability of type 1 EBNA-2 to induce a key group of cell genes and the EBV LMP-1 gene, which mediate the growth advantage of B cells infected with type 1 EBV. The EBNA-2 binding sites in these cell genes have a sequence motif similar to the sequence known to mediate regulation of the EBV LMP-1 promoter. Further detailed analysis of transactivation and promoter binding provides new insight into the physiological regulation of cell genes by EBNA-2.